2013
DOI: 10.1016/j.ramb.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Impressões de pacientes, médicos e estudantes de Medicina quanto a aparência dos médicos

Abstract: Brazilian patients, physicians, and medical students form a better initial impression of physicians using clothing traditionally associated with the profession and exhibiting more conventional appearance. The use of entirely white garments appears to be a satisfactory option in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
0
17
0
5
Order By: Relevance
“…En Sudamérica, un reporte argentino 23 demostró que tanto acompañantes y niños mayores de seis años preferían la atención de un médico usando delantal blanco, incluso 88% de los niños rechazaría la atención de un médico pediatra que no lo usara. Un estudio brasileño 24 demostró también una elección prioritaria de uso de ropa blanca (polera y pantalón) condicionado por las altas temperaturas que los médicos se ven expuestos en mayor parte del año.…”
Section: Discussionunclassified
“…En Sudamérica, un reporte argentino 23 demostró que tanto acompañantes y niños mayores de seis años preferían la atención de un médico usando delantal blanco, incluso 88% de los niños rechazaría la atención de un médico pediatra que no lo usara. Un estudio brasileño 24 demostró también una elección prioritaria de uso de ropa blanca (polera y pantalón) condicionado por las altas temperaturas que los médicos se ven expuestos en mayor parte del año.…”
Section: Discussionunclassified
“…A study performed at a school hospital located in the southeastern region of Brazil revealed that its participants consider a good presentation is important for students and professionals in the medical area before and during contact with the patient. Equally desirable are behaviors and attitudes capable of contributing to a quality personal and professional image [22].…”
Section: Discussionmentioning
confidence: 99%
“…Among the many characteristics listed by the father of medicine, the dignified appearance was highlighted in the scene above and has been an element of research for doctors and medical students. 8 In this scene, again, it is necessary to contextualize the reactions of the characters in the 27 years since the movie was released.…”
Section: Dadmentioning
confidence: 99%